Scaling Up Early Infant Male Circumcision: Lessons From the Kingdom of Swaziland - Fitzgerald, Laura (Glob Health Sci Pract, 2016)
BACKGROUND: The government of the Kingdom of Swaziland recognizes that it must urgently scale up HIV prevention interventions, such as voluntary medical male circumcision (VMMC). Swaziland has adopted a 2-phase approach to male circumcision scale-up. The catch-up phase prioritizes VMMC services for adolescents and adults, while the sustainability phase involves the establishment of early infant male circumcision (EIMC). Swaziland does not have a modern-day tradition of circumcision, and the VMMC program has met with client demand challenges. However, since the launch of the EIMC program in 2010, Swaziland now leads the Eastern and Southern Africa region in the scale-up of EIMC. Here we review Swaziland’s program and its successes and challenges. METHODS: From February to May 2014, we collected data while preparing Swaziland’s “Male Circumcision Strategic and Operational Plan for HIV Prevention 2014–2018.” We conducted structured stakeholder focus group discussions and in-depth interviews, and we collected EIMC service delivery data from an implementing partner responsible for VMMC and EIMC service delivery. Data were summarized in consolidated narratives. RESULTS: Between 2010 and 2014, trained providers performed more than 5,000 EIMCs in 11 health care facilities in Swaziland, and they reported no moderate or severe adverse events. According to a broad group of EIMC program stakeholders, an EIMC program needs robust support from facility, regional, and national leadership, both within and outside of HIV prevention coordination bodies, to promote institutionalization and ownership. Providers and health care managers in 3 of Swaziland’s 4 regional hospitals suggest that when EIMC is introduced into reproductive, maternal, newborn, and child health platforms, dedicated staff attention can help ensure that EIMC is performed amid competing priorities. Creating informed demand from communities also supports EIMC as a service delivery priority. Formative research shows that EIMC programs should address the fears and anxieties of parents so that they, especially fathers, understand the health benefits of EIMC before the birth of their babies. CONCLUSION: The vast majority of public-sector facilities in Swaziland are led by nurses, and nurses and midwives have borne the brunt of caring for patients with HIV/AIDS in Swaziland. Like prevention of mother-to-child transmission, EIMC provides an opportunity for nurses and midwives to stand at the forefront of HIV prevention efforts. Rapid scale-up of VMMC and EIMC in Swaziland has the potential to avert more than 56,000 HIV infections and save US$370 million in the next 20 years.